2010
DOI: 10.1088/0953-8984/22/23/235903
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of domain distribution in SrTiO3—competing effects of applied electric field and mechanical stress

Abstract: Below its ordering temperature at 105 K, perovskite-type SrTiO(3) exhibits a tetragonal phase with three different structural domains that are strongly influenced by the application of uniaxial mechanical stresses and electric fields. A careful neutron diffraction study of superlattice reflections provides full quantitative information about the varying domain distributions under external loads as a function of temperature. It is shown that electric field and uniaxial stress exhibit competitive effects and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 27 publications
1
21
0
5
Order By: Relevance
“…They may also become electrically conducting due to the charge injected into them from the gate [17]. Though a transition to an orthorhombic ferroelectric phase of STO has been deduced from analysis of neutron diffraction superlattice reflections under applied field or strain [8], to the best of our knowledge, this is the first observation in real space of E-field-induced ferroelectric twin walls in a nonferroelectric bulk material.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…They may also become electrically conducting due to the charge injected into them from the gate [17]. Though a transition to an orthorhombic ferroelectric phase of STO has been deduced from analysis of neutron diffraction superlattice reflections under applied field or strain [8], to the best of our knowledge, this is the first observation in real space of E-field-induced ferroelectric twin walls in a nonferroelectric bulk material.…”
mentioning
confidence: 76%
“…STO is cubic at room temperature, but undergoes a ferroelastic transition to tetragonal structure at around 105 K. It does not become spontaneously ferroelectric at low temperatures despite its huge permittivity [6,7]. Nevertheless, electric order can be induced by stress, or by electric field (E) [8][9][10] at a threshold of 1.40 kV=cm at ∼5 K.When STO is used as a substrate or gate insulator for materials such as topological insulators and superconductors [11,12], films grown on STO are assumed to be biased uniformly. However, this is not really the case as nonuniformity can arise from the tetragonal domain structure.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Only by isotope substitution [8], by the application of mechanical stress [4] or an electric field [6] a ferroelectric phase can be induced below about 40 K which can be described by the spontaneous polarization as the order parameter. Recently, we observed that an applied electric field does not only favor the polar phase but is also able to change the domain structure of the tetragonal phase [14]. This is particularly surprising since the electric field and the tetragonal order parameter exhibit different symmetry properties.…”
Section: Introductionmentioning
confidence: 94%